Catalytic cracking catalyst with non-uniformly distributed active components and preparation method thereof
By using non-uniformly distributed active components design in the FCC catalyst, and using materials such as binders, nucleating substances and molecular sieves, a catalyst with an average particle size of 60-100 microns was prepared, which solved the problems of long diffusion distance and low reaction efficiency caused by uniform distribution of active components and substrates in the prior art, and achieved higher liquefied gas and gasoline yields and better product distribution.
Patent Information
- Application Number
- CN202411906177.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-06-27
AI Technical Summary
In the existing FCC catalysts, the uniform distribution of the active components and the matrix leads to a long diffusion distance, low reaction efficiency, and difficult to effectively reduce the yield of dry gas and coke.
25%-30% binder, 5%-30% nucleating substance and 25%-40% molecular sieve were used to prepare a catalyst with kaolin, and a catalyst with an average particle size of 60-100 microns was prepared by spray drying and calcining to achieve non-uniform distribution of active components.
Through the non-uniform distribution of active components, the diffusion distance between reactants and products is shortened, the probability of secondary reaction of oil products is reduced, the utilization rate of active components is improved, the yield of liquefied gas and gasoline is significantly improved, and the product distribution is improved.
Smart Images

Figure CN120205214A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of the preparation of fluid catalytic cracking catalysts, and particularly relates to a fluid catalytic cracking catalyst with non-uniform distribution of active components and a preparation method thereof. Background Art
[0002] Fluid catalytic cracking (FCC) is the most basic oil refining process for converting heavy hydrocarbon feeds into light products such as liquefied petroleum gas, gasoline, and diesel. The development of the FCC process has always been closely linked to the development of FCC catalysts, and the two promote and complement each other.
[0003] The FCC unit mainly includes a reactor and a regenerator, and its operation mode is a cyclic mode. Reactants and solid catalysts enter from the bottom of the reactor together and undergo cracking reactions to generate various different products during the upward movement. The main products include target products such as liquefied petroleum gas, gasoline, and diesel, as well as non-target products such as dry gas, coke, and slurry. The gaseous and liquid products are separated from the catalyst at the top of the reactor. The catalyst containing the coke generated by the reaction enters the regenerator, and the coke deposited on the catalyst is burned off with air to restore the activity of the catalyst. After the activity is restored, the catalyst is recycled back to the bottom of the reactor to carry out the next cycle together with the catalytic feedstock.
[0004] Modern FCC catalysts mainly consist of two major parts: active component molecular sieves and matrix. The active component is Y-type molecular sieve, and the matrix generally consists of filler kaolin and various silica-alumina binders. The preparation process of the catalyst is as follows: the molecular sieve, kaolin, and binder are mixed and slurried, and the molecular sieve and filler kaolin are bonded together through the binder, and then spray-dried to form a solid catalyst product with certain strength and particle size requirements. The particle size of the catalyst is about 20 - 200 microns, and the average particle size is about 60 - 100 microns.
[0005] For the FCC catalysts prepared conventionally, the active component molecular sieves and the matrix are uniformly distributed with each other, that is, the molecular sieves are uniformly distributed on the surface and in the bulk of the catalyst microspheres. The function of the catalyst is to crack heavy oil products with large molecular weights into the required light products with smaller molecular weights. The two most important steps of the cracking reaction are the adsorption and diffusion of reactant molecules on the catalyst and the desorption and diffusion of product molecules on the catalyst. How to reduce the diffusion distance and increase the diffusion speed is an important factor for improving the product distribution.
[0006] In order to solve the above problems, it is urgent to invent a fluid catalytic cracking catalyst with non-uniform distribution of active components and a preparation method thereof to solve the above problems. Summary of the Invention
[0007] The object of the present invention is to provide a catalytic cracking catalyst with non-uniform distribution of active components and a preparation method thereof. The catalyst of the present invention is made of 25%-30% binder, 5%-30% nucleating substance, 25%-40% molecular sieve and kaolin, and the particle size of the nucleating substance is controlled to be 33-44 microns, and the particle size of the prepared catalyst is 60-100 microns. The present invention improves the reaction conversion rate through the catalyst for catalytic cracking reaction, and solves the above technical problems existing in the prior art.
[0008] A catalytic cracking catalyst with non-uniform distribution of active components disclosed by the present invention, the catalyst material includes: 25%-30% binder, 5%-30% nucleating substance and 25%-40% molecular sieve, and the rest is filler kaolin.
[0009] Preferably, the nucleating substance is an inert substance, and the inert substance is used as the microsphere particle egg nucleus. The nucleating substance includes α-aluminum oxide and / or mullite, the particle size of the nucleating substance is 33-44 microns, and the average particle size of the finished catalyst is 60-100 microns.
[0010] Preferably, the preparation method of the catalytic cracking catalyst includes: mixing kaolin, molecular sieve slurry, binder and nucleating substance into a slurry and mixing evenly, then spray drying and forming, washing, filtering and drying. The preparation steps include:
[0011] S1: Mix kaolin with deionized water and beat into a slurry for dispersion for 60 minutes;
[0012] S2: Add the binder and beat into a slurry for 60-80 minutes;
[0013] S3: Add the nucleating substance and beat into a slurry for 60-100 minutes;
[0014] S4: Add the ground molecular sieve slurry and stir for 30-60 minutes;
[0015] S5: Spray dry the catalyst slurry, calcine the catalyst microspheres at 500°C for 30 minutes, the average particle size meets 60-100μm, and the attrition index ≤ 2.5%;
[0016] S6: Wash, filter and dry the obtained catalyst microspheres.
[0017] Preferably, the binder is a composite binder composed of aluminum sol and pseudo-boehmite. Among them, the aluminum sol: Al 11-12m%, AlCl 1.1-1.2m%, PH2.2-2.8; the pseudo-boehmite is calcined to 64%.
[0018] Preferably, in step S2, pseudoboehmite is added to the kaolin after mixing and beating, and at the same time hydrochloric acid is added for acidification treatment for 30 minutes, and then aluminosol is added to the acidified mixture.
[0019] Preferably, in step S4, the molecular sieve is selected as Y-type zeolite with a unit cell parameter of 24.62 and an RE2O3 content of 9.0%.
[0020] Preferably, in step S6, after the catalyst microspheres are calcined at 500 °C for 30 minutes, they are washed with deionized water of the dry-based catalyst.
[0021] Beneficial effects
[0022] The object of the present invention is to provide a fluid catalytic cracking catalyst with non-uniform distribution of active components and its preparation method. By making the active components uniformly distributed in the eggshell layer of the catalyst, and the egg core is an inert substance with a low surface area, the product distribution of the FCC process is greatly improved. The advantages of this invention compared with the traditional catalyst process are as follows:
[0023] 1. The active components are distributed in the eggshell layer, shortening the diffusion distance of reactants and products, reducing the probability of secondary reactions of oil products, and reducing the yields of dry gas and coke.
[0024] 2. Under the condition of the same active component content in the present invention, the active components are distributed in the eggshell layer, improving the utilization rate of the active components. When the particle size of the nucleating substance is controlled to be 33-44 microns, the reaction conversion rate of the produced catalyst is higher, greatly increasing the yields of liquefied gas and gasoline. Brief description of the drawings
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only the embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on the provided drawings.
[0026] Figure 1 It is the preparation steps of the fluid catalytic cracking catalyst of the present invention. Detailed embodiments
[0027] A fluid catalytic cracking catalyst with non-uniform distribution of active components and its preparation method disclosed by the present invention. The catalyst material disclosed by the present invention includes: 25%-30% of binder, 5%-30% of nucleating substance, and 25%-40% of molecular sieve, and the rest is filler kaolin.
[0028] In some embodiments, the nucleating substance is an inert substance, and the inert substance is used as the egg nucleus of the microsphere particles. The nucleating substance includes α-aluminum oxide and / or mullite, the particle size of the nucleating substance is 33-44 microns, and the average particle size of the finished catalyst is 60-100 microns.
[0029] In some embodiments, the method for preparing the fluid catalytic cracking catalyst includes: slurrying and mixing kaolin, molecular sieve slurry, binder and nucleating substance evenly, and then spray-drying, forming, washing, filtering and drying. The preparation steps sequentially include:
[0030] S1 Mix kaolin with deionized water and slurry and disperse for 60 minutes;
[0031] S2 Add the binder and slurry for 60-80 minutes;
[0032] S3 Add the nucleating substance and slurry for 60-100 minutes;
[0033] S4 Add the ground molecular sieve slurry and stir for 30-60 minutes;
[0034] S5 Spray-dry the catalyst slurry, calcine the catalyst microspheres at 500°C for 30 minutes, the average particle size meets 60-100 μm, and the attrition index ≤ 2.5%;
[0035] S6 Wash, filter and dry the obtained catalyst microspheres.
[0036] In some embodiments, deionized water is added during the slurrying of kaolin. The use of deionized water avoids the reaction of impurity ions in water with the components in the catalyst, which affects the quality and conversion rate of the catalyst.
[0037] In some embodiments, the binder is a composite binder composed of aluminum sol and pseudo-boehmite. Among them, the aluminum sol: Al 11-12m%, AlCl 1.1-1.2m%, PH 2.2-2.8;
[0038] The pseudo-boehmite is calcined to 64%.
[0039] In some embodiments, the molecular sieve is Y-type zeolite. The unit cell parameter of the selected Y-type zeolite is 24.62, the RE2O3 content is 9.0%, RE2O3 is a rare earth oxide, RE2O3 is a basic oxide, and RE can be nickel, scandium, yttrium, lanthanum, etc.
[0040] In some embodiments, in step S2, pseudo-boehmite is added to the kaolin after mixing and slurrying, and at the same time hydrochloric acid is added for acidification treatment for 30 minutes, and then aluminum sol is added to the acidified mixed solution.
[0041] The specifications of the raw materials used in the examples are as follows:
[0042] Kaolin: Produced by China Kaolin Company. After calcination of the kaolin, the mass of the remaining substance accounts for 72% of the mass of the original kaolin;
[0043] Molecular sieve: Y-type zeolite, produced by Sichuan Runhe Catalytic New Materials Co., Ltd. The unit cell parameter of the molecular sieve is 24.62, and the RE2O3 content is 9.0%;
[0044] Aluminum sol: Produced by Jilin Pinqian Chemical Technology Development Co., Ltd. Al is 11 - 12m%, AlCl is 1.1 - 1.2m%, and PH is 2.2 - 2.8;
[0045] Pseudoboehmite: Produced by Yueyang Changke Chemical Co., Ltd. After calcination of the pseudoboehmite, the mass of the remaining substance accounts for 64% of the mass of the original pseudoboehmite;
[0046] The nucleating substance is selected as α-aluminum oxide: Produced by Zibo Kaiou Chemical Co., Ltd., with a particle size of 44μm, α-Al2O3 > 93%, and Al2O3 > 99.5%.
[0047] Example 1
[0048] To prepare an eggshell-type active component catalyst with 30% molecular sieve content, take 4.86 kg of kaolin, add 12.1 kg of deionized water, mix and beat for 60 minutes, add 2.34 kg of pseudoboehmite, add 374 g of 20% hydrochloric acid, conduct acidification treatment for 30 minutes, add 4.17 kg of aluminum sol, beat for 40 minutes, add 1 kg of the nucleating substance α-aluminum oxide, beat for 40 minutes, add 10 kg of the molecular sieve slurry ground by a colloid mill (with a 30% residue on ignition), beat for 30 minutes, with the solid content of the slurry being 29%, conduct spray drying, roast the obtained catalyst microspheres at 500°C for 30 minutes, then wash twice with deionized water 5 times the dry basis catalyst, and dry at a constant temperature of 120°C for 2 hours, which is the sample of Example 1, sample number A. The mass ratio of the molecular sieve content, binder, and nucleating substance in the catalyst is: 30% Y-type molecular sieve / 25% binder / 10% nucleating substance / 35% kaolin.
[0049] Example 2
[0050] Compared with Example 1, for the sample of Example 2, sample number B, the mass ratio of the molecular sieve content, binder, and nucleating substance in the catalyst is: 30% Y-type molecular sieve / 25% binder / 20% nucleating substance / 25% kaolin.
[0051] Example 3
[0052] Compared with Example 1, for the sample of Example 3, sample number C, the mass ratio of the molecular sieve content, binder, and nucleating substance in the catalyst is: 30% Y-type molecular sieve / 25% binder / 30% nucleating substance / 15% kaolin.
[0053] Example 4
[0054] To prepare an eggshell-type active component catalyst with a molecular sieve content of 40%, take 2.78 kg of kaolin, add 10 kg of deionized water, mix and beat for 60 minutes, add 3.13 kg of pseudo-boehmite, add 500 g of 20% hydrochloric acid, perform acidification treatment for 30 minutes, add 4.17 kg of aluminum sol, beat for 40 minutes, add 1 kg of nucleating substance α-alumina, beat for 40 minutes, add 13.33 kg of molecular sieve slurry ground by a colloid mill (residual ash 30%), beat for 30 minutes, the solid content of the slurry is 29%, spray dry, and the obtained catalyst microspheres are calcined at 500 °C for 30 minutes, then washed twice with deionized water 5 times the dry-based catalyst, and dried at a constant temperature of 120 °C for 2 hours to obtain the sample of Example 4, sample number D. The molecular sieve content, binder and nucleating substance of the catalyst are: 40% Y-type molecular sieve / 30% binder / 10% nucleating substance / 20% kaolin.
[0055] Example 5
[0056] Compared with Example 4, for the sample of Example 5, sample number E, the molecular sieve content, binder and nucleating substance of the catalyst are: 40% Y-type molecular sieve / 30% binder
[0057] / 20% nucleating substance / 10% kaolin.
[0058] Example 6
[0059] Compared with Example 4, for the sample of Example 6, sample number F, the molecular sieve content, binder and nucleating substance of the catalyst are: 40% Y-type molecular sieve / 30% binder
[0060] / 25% nucleating substance / 5% kaolin.
[0061] Example 7
[0062] Under the condition of the same material ratio, that is, the overall catalyst ratio is 40% Y-type molecular sieve / 30% binder / 25% nucleating substance / 5% kaolin, to prepare eggshell-type active component catalysts with different particle sizes of the nucleating substance. Take 0.694 kg of kaolin, add 10 kg of deionized water, mix and beat for 60 minutes, add 3.13 kg of pseudo-boehmite, add 500 g of 20% hydrochloric acid, carry out acidification treatment for 30 minutes, add 4.17 kg of aluminum sol, beat for 40 minutes, add 2.5 kg of α-aluminum oxide with a nucleating substance particle size of 44 μm, beat for 40 minutes, add 13.33 kg of molecular sieve slurry ground by a colloid mill (residual ash 30%), beat for 30 minutes, the solid content of the slurry is 29%, spray drying, the obtained catalyst microspheres are calcined at 500 °C for 30 minutes, then washed twice with deionized water 5 times the dry-based catalyst, and dried at a constant temperature of 120 °C for 2 hours, which is the sample of Example 7, and the sample number is F.
[0063] Example 8
[0064] Compared with Example 7, α-aluminum oxide with a nucleating substance particle size of 21 μm is selected to participate in the reaction in Example 8. The sample of Example 8 has the sample number G.
[0065] Example 9
[0066] Compared with Example 7, α-aluminum oxide with a nucleating substance particle size of 33 μm is selected to participate in the reaction in Example 9. The sample of Example 9 has the sample number H.
[0067] Example 10
[0068] Compared with Example 7, α-aluminum oxide with a nucleating substance particle size of 65 μm is selected to participate in the reaction in Example 10. The sample of Example 10 has the sample number I.
[0069] Comparative Example 1
[0070] Comparative Example 1 is the preparation process of a dual-aluminum binder FCC catalyst of pseudo-boehmite plus aluminum sol. The molecular sieve content is 30%. Add 4.17 kg of aluminum sol into the reaction kettle, add 11.7 kg of deionized water, beat, add 2.34 kg of pseudo-boehmite, beat for 20 minutes, add 6.25 kg of kaolin, stir and beat for 40 minutes, then add 374 g of 20% hydrochloric acid, stir for 30 minutes, add 10 kg of REUSY molecular sieve slurry ground by a colloid mill, spray dry after beating for 30 minutes, calcine the obtained catalyst microspheres at 500 °C for 30 minutes, then add 8 times deionized water, stir evenly, wash at 80 °C for 15 minutes, filter and dry to obtain the finished product, numbered DB-1.
[0071] Comparative Example 2
[0072] Comparative Example 2 is the preparation process of a dual-aluminum binder FCC catalyst with pseudo-boehmite and aluminum sol. The molecular sieve content is 40%. In a reaction kettle, 4.17 kg of aluminum sol is added, 9.69 kg of deionized water is added, and they are stirred. Then 3.13 kg of pseudo-boehmite is added. After beating for 20 minutes, 4.17 kg of kaolin is added. After stirring and beating for 40 minutes, 500 g of hydrochloric acid with a concentration of 20% is added, and they are stirred for 30 minutes. Then 13.33 kg of REUSY molecular sieve slurry ground by a colloid mill is added. After beating for 30 minutes, it is spray-dried. The obtained catalyst microspheres are calcined at 500 °C for 30 minutes, then 8 times of deionized water is added, stirred evenly, washed at 80 °C for 15 minutes, filtered and dried to obtain the finished product, numbered DB-2.
[0073] Test Example 1
[0074] The comparison of the physical and chemical properties and reaction performance between Examples 1-3 and Comparative Example 1: The specific surface area and pore volume were measured by the low-temperature nitrogen adsorption BET method using an ASAP-2400 adsorption instrument. The microactivity was measured using a RIPP standard light oil microreactor device. The product distribution was evaluated using a small fixed fluidized bed. The feedstock oil was the catalytic feed of Shandong Tianhong Chemical Co., Ltd. The feedstock properties are shown in Table 1. The evaluation conditions were a reaction temperature of 500 °C, a catalyst-to-oil ratio of 5.0, and a space velocity of 20 h-1. The catalyst was deactivated by aging treatment at 800 °C for 17 hours with 100% steam.
[0075] Table 1 Data table of the feedstock properties of the Tianhong Chemical catalytic cracking unit.
[0076]
[0077]
[0078] Table 2 is a data table for comparing the performance between Examples 1-3 and Comparative Example 1.
[0079]
[0080]
[0081] The data in Table 2 show that compared with the catalysts prepared by the prior art, the catalyst prepared by the method of the present invention has a higher utilization rate of active components, that is, as the nucleating substance increases from 10% to 30%, the microactivity increases significantly. The evaluation of the product distribution in the fixed fluidized bed shows that the catalyst of the present invention has higher yields of liquefied gas and gasoline and better coke selectivity, and the total light liquid yield (liquefied gas + gasoline + diesel) is also higher.
[0082] Test Example 2
[0083] Table 3 is a data table for comparing the physical and chemical properties and reaction performance between Examples 4-6 and Comparative Example 2.
[0084]
[0085]
[0086] The data in Table 3 show that as the content of the active component of the catalyst increases from 30% in Examples 1-3 to 40% in Examples 4-6, the conversion rate increases significantly, and the yield of valuable products also increases significantly. Comparing Examples D, E, and F with Comparative Example DB-2, the trend of product distribution improvement is consistent with that of Test Example 1, that is, as the nucleating substance increases, the micro-reactivity increases, and the yields of liquefied gas, gasoline, and total light liquid gradually increase, and the coke selectivity improves.
[0087] Table 4 is a comparison data table of the physical and chemical properties and reaction performance of Examples G, H, I, and F.
[0088]
[0089]
[0090]
[0091] For eggshell-type active component catalysts made of nucleating substances with different particle sizes under the same formula, there are differences in reaction performance. The required average particle size of the finished catalyst is between 60 and 100 microns. Under this condition limit, using nucleating substances and active components with different particle sizes will show a trend of one increasing while the other decreasing. That is, the larger the particle size of the nucleating substance, the less active component attached to the catalyst particles, and the corresponding cracking ability will decrease; conversely, it will reduce the accessibility of the active component and fail to meet the performance requirements. From the above data, it can be seen that when the particle size of the nucleating substance is between 33 and 44 microns, the reaction performance is better than that of other examples.
[0092] Compared with the catalysts prepared by the prior art, the catalyst prepared by the method of the present invention has a higher utilization rate of the active component. That is, as the nucleating substance increases from 10% to 30%, the micro-reactivity increases significantly. When the nucleating substance reaches 40%, the conversion rate increases significantly, and the yield of valuable products also increases significantly. In the prior art, common catalytic reactions occur on the surface of the catalyst. Smaller particle sizes have a larger specific surface area and higher reaction conversion rates. However, this experimental study shows that the conversion rate when the particle size of the nucleating substance is between 33 and 44 microns is higher than that when the particle size of the nucleating substance is less than 33 microns and when the particle size of the nucleating substance is greater than 44 microns. When the particle size of the nucleating substance is between 33 and 44 microns, the conversion rate of the catalytic cracking reaction is higher.
[0093] The above content is a further detailed description of the present invention in combination with specific preferred embodiments. It cannot be determined that the specific embodiments of the present invention are limited thereto. For those of ordinary skill in the technical field to which the present invention pertains, without departing from the present invention, several simple deductions or substitutions can still be made, and all should be regarded as falling within the scope of patent protection determined by the claims submitted for the present invention.
Claims
1. A catalytic cracking catalyst having a non-uniform distribution of active components, characterized in that: The catalyst material comprises: 25%-30% of a binder, 5%-30% of a nucleating material and 25%-40% of a molecular sieve, and the rest is filler kaolin.
2. A catalytic cracking catalyst with non-uniform distribution of active components according to claim 1, characterized in that: The nucleating material is an inert material, which is used as the core of the microsphere particles. The nucleating material includes α-alumina and / or mullite. The particle size of the nucleating material is 33-44 microns, and the average particle size of the finished catalyst is 60-100 microns.
3. The method for preparing a catalytic cracking catalyst with non-uniform distribution of active components according to claim 2, characterized in that: The method for preparing the catalytic cracking catalyst comprises: slurrying and mixing kaolin, molecular sieve slurry, binder and nucleating material uniformly, spray drying and forming, washing, filtering and drying, and the preparation steps include: S1: Mix kaolin and deionized water and slurry for 60 minutes; S2: Add binder and beat for 60-80 minutes; S3: adding nucleating material and beating for 60-100 minutes; S4: Add the ground molecular sieve slurry and stir for 30-60 minutes; S5: The catalyst slurry is spray dried, and the catalyst microspheres are calcined at 500°C for 30 minutes, with an average particle size of 60-100 μm and an abrasion index of ≤2.5%; S6: washing, filtering and drying the obtained catalyst microspheres.
4. The method for preparing a catalytic cracking catalyst with non-uniform distribution of active components according to claim 3, characterized in that: The binder is a composite binder composed of aluminum sol and pseudo-boehmite, wherein the aluminum sol has Al 11-12m%, AlCl 1.1-1.2m%, and pH 2.2-2.8; the pseudo-boehmite is burned to a residue of 64%.
5. The method for preparing a catalytic cracking catalyst with non-uniform distribution of active components according to claim 4, characterized in that: In the step S2, pseudo-boehmite is added to the mixed and pulped kaolin, and hydrochloric acid is added to perform acidification for 30 minutes, and aluminum sol is added to the acidified mixed solution.
6. The method for preparing a catalytic cracking catalyst with non-uniform distribution of active components according to claim 5, characterized in that: In the step S4, the molecular screening uses Y-type zeolite, with a unit cell parameter of 24.62 and a RE2O3 content of 9.0%.
7. The method for preparing a catalytic cracking catalyst with non-uniform distribution of active components according to claim 5, characterized in that: In the step S6, the catalyst microspheres are calcined at 500° C. for 30 minutes and then washed with deionized water of the dry catalyst.